Use of wound soaker catheters in pain management. Issue 1 (11th January 2013) - Armitage‐Chan, Elizabeth
Abstract : Wound soaker catheters provide a useful method for administering local anaesthetic direct to the wound site, avoiding the problems that come with regular administration, such as a limited duration of action or lack of available nerve blocks. This article describes the use of wound soaker catheters, explains their advantages and includes some practical tips for the clinician.